A "Trojan Horse" in the peer-review process of fee-charging economic journals. Issue 3 (August 2020) - Dell'Anno, Roberto; Caferra, Rocco; Morone, Andrea
Highlights: How trustworthy is the editorial process in fee-charging journals? Our study reveals the poor quality standards applied by some Open Access Journals, which require Article Processing Charges. Not all Article Processing Charges Journals are predatory. There is a (too) large presence of predatory journals among Article Processing Charges Journals. Abstract: This paper aims to unmask the inadequacy of the review process of a sample of fee-charging journals in economics. We submitted a bait-manuscript to 104 academic economic journals to test whether there is a difference in the peer-review process between Article Processing Charges (APC) journals and Traditional journals which do not require a publication fee. The submitted bait-article was based on completely made-up data, with evident errors in terms of methodology, literature, reporting of results, and quality of language. Nevertheless, about half of the APC journals fell in the trap. Their editors accepted the article in the journals and required to pay the publication fee. We conclude that the Traditional model has a more effective incentive-mechanism in selecting articles, based on quality standards. Otherwise, we confirm that the so-called "Predatory Journals" – i.e. academic journals which accept papers without a quality check – exploit the APC scheme to increase their profits. They are also able to enter whitelists (e.g. Scopus, COPE). Accordingly, poor-quality articles published on APC journals shed the light on the weakness of methodologies based on a mechanical inclusion of academic journals in scientific database indexes, succeeding in being considered for bibliometric evaluations of research institutions or scholars' productivity.